The Roles of Capital Intensity in Moderating Managerial Ownership and Investment Opportunity Set (IOS) on Accounting Conservatism - Sholikhah, Zahrotus; Baroroh, Niswah (Accounting Analysis Journal, 2021)
This study aims to examine the effect of managerial ownership and investment opportunity set (IOS) on accounting conservatism with capital intensity as a moderating variable. The population was the manufacturing companies listed in the Indonesia Stock Exchange (IDX) from 2016-2018 as many as 184 companies. The sampling technique was purposive sampling technique and selected 39 units of analysis from 16 companies. The collection of research data used documentation technique. The analysis of research data used descriptive statistics and inferential statistics. The hypothesis testing used moderating regression analysis with an absolute difference test using IBM SPSS 24 tools. The results showed that investment opportunity set (IOS) had a significant positive effect while managerial ownership did not affect on accounting conservatism. Capital intensity could not significantly moderate the effect of managerial ownership and investment opportunity set (IOS) on accounting conservatism. Based on the result of this research, the conclusion is investment opportunity set (IOS) has a significant positive effect on accounting conservatism. The companies with higher investment opportunity sets (IOS) are able to increase the application of the accounting conservatism principles. Keyword: Accounting Conservatism; Managerial Ownership; Investment Opportunity Set (IOS); Capital Intensity